Dark Web and Cryptocurrency - Bolatov, Nugerbek (Jihočeská univerzita, 2023)
This study aims to explore the principle of the interdependence and mutual influence of the Dark web and cryptocurrency. Specifically, it explores the terms "the Dark web" and "cryptocurrency", as well as distinguishes cryptocurrency from normal currency. Furthermore, it establishes a connection between the Dark web and cryptocurrency. In order to reach the aim of this study, multiple sources of literature had been analyzed, including books and online articles. The analysis of literature shows that there is a strong correlation between the existence of the Dark web and demand on cryptocurrency. Thus, the results of this paper conclude that the Dark web and cryptocurrency exist in symbiosis - cryptocurrency allows the Dark web to exist for its anonymity and impunity, while the Dark web guarantees demand on cryptocurrency.
Dark Web and Cryptocurrency
Keywords: currency; cryptocurrency; the Internet; the Dark web; anonymity; illegal; currency; cryptocurrency; the Internet; the Dark web; anonymity; illegal